The Development of Knowledge Management-Based Behavior Tracking App - Suhendra; Eka Suhardi; Widodo Sunaryo; Ahmad Arif Fadilah (Universitas Pendidikan Ganesha, 2025)
Counseling teachers and guardians class own role important in monitor and record behavior students. Needed a accurate application for take notes behavior the purpose of the research this for develop application logger behavior the student who was called with application logger behavior based on management knowledge. Recording results this then published and accessed by parents students. Research methods use Research and Development (R&D) with stages: study literature, analysis needs, development products, and trials product. Subject study This is a guidance teacher counseling and guardianship class. Validation test results by experts materials, IT experts, and management showed an average of 96%, 88.4%, and 94%; which are in the very good criteria. This is prove that application suppressor behavior this worthy for developed. The results of the evaluation carried out towards the related teachers use; addition insight, and usefulness application this, an average of 44% of teachers stated that they strongly agreed and 52% stated that they agree, and 4% stated no agree. The evaluation was carried out towards the parents of the students concerned usability, accuracy recording, and transparency access information by party school, 48% of parents strongly agree, 50% of parents agree, and 2% of parents do not agree. Test results this show that application can take notes behavior student in a way accurate and precise. Research conclusion prove that application this can help teachers and guardians class take notes behavior student in a way accurate and reporting to parents. School can utilise notes behavior student as base takeover decision. Implications study This make it easier for teachers and guardians class know behavior student in a way real time and become base evaluation for to plant behavior good student.